Yiqi Huoxue recipe ameliorates diabetic nephropathy by mediating VAPB–PTPIP51 complex to activate autophagy and regulate MAM contact - Dai, Linghao; Wang, Mengyi; Wang, Bo; Liang, Haowei; Guan, Yang; Du, Zhongyan; Wang, Hui (Frontiers in Nutrition, 2025)
BackgroundDiabetic nephropathy (DN), a major complication of diabetes mellitus (DM), poses a high mortality and a global health burden. Mitochondria-associated endoplasmic reticulum membranes (MAMs) and mediated autophagy are regarded as the crucial factors in the development of DN. The Yiqi Huoxue recipe (YHR), a traditional Chinese medicine formula, has been reported to treat DN and regulate autophagy, while its underlying mechanism remains unclear.MethodsFirstly, UPLC-MS/MS analysis was performed to identify the chemical components of YHR. Then, C57BL/6 J mice were injected with streptozotocin and fed with high-fat diet to induce DN. YHR (7.8, 15.6 g/kg/d) was administered via intragastric gavage for 8 weeks. Biochemical parameters and oxidative stress indicators were measured; H&E, PAS, and immunohistochemistry staining of nephrin were performed. Mitochondrial Ca2+ levels were assessed by flow cytometry, while autophagosomes and MAMs were examined using transmission electron microscopy (TEM). The expression levels of VAPB, PTPIP51, LC3 II/I, P62 were detected by Western blot. Podocytes overexpressing PTPIP51 or VAPB were analyzed for cell activity using the CCK-8 assay, autophagy flux by TEM, and the expression of LC3 II/I and P62 by Western blot. In si-PTPIP51-transfected and high-glucose (HG)-stimulated podocytes, CCK-8 assay, PCR, TEM, and immunofluorescence staining were performed to detect the YHR-containing serum on cell activity, mtDNA, MAMs, autophagosomes and LC3 expression.ResultsThe chemical fingerprint of YHR was constructed and composed chemicals were identified. In DN mice, YHR treatment reduced the elevated fasting blood glucose (FBG), total cholesterol (TC), triglycerides (TG), blood urea nitrogen (BUN), serum creatinine (Scr), urinary albuminuria (ALB), and microscale albuminuria (MAU) levels. It also alleviated kidney and glomerulus damage, mitochondrial Ca2+, oxidative stress, MAM abnormal contact, and activated autophagy. The enhanced expression of MAM complex, VAPB–PTPIP51, were also inhibited in YHR-treated groups. The cell activity and autophagosome formation were significantly inhibited in podocytes overexpressing PTPIP51 (oe-PTPIP51) and VAPB (oe-VAPB). In contrast, in HG-podocytes, si-PTPIP51 promoted the cell activity, mtDNA copy number, MAM contact, autophagosomes formation and LC3 expression. More importantly, the addition of YHR-containing serum enhanced this effect.ConclusionYHR may protect kidneys in DN by regulating the MAM complex VAPB–PTPIP51 to trigger autophagy, providing insights into TCM’s clinical application and DN drug development.